PENGEMBANGAN BUKU AJAR PADA SUBTEMA AKU MERAWAT TUBUHKU KELAS I SEKOLAH DASAR BERBASIS GAMBAR LINGKUNGAN SEKITAR - Santya Dian Pratiwi; Arya Setya Nugroho; Nanang Khoirul Umam (JUSEDA, 2021)
This research aims to know the development of textbooks on subtheme I treat my body in grade I elementary school based on picture of the surrounding environment., and knowing validity of textbooks on subtheme I treat my body in grade I elementary school based on picture of the surrounding environment. This research implemented at UPT SD Negeri 131 Gresik. The model used is the model developed by Thiagarajan that is 4-D model with the modification of the researcher into three stages including the defining stage (define), design (design), dan develop (develop). Data analysis used is the validity analysis of textbooks. Aspecta assessed are aspects of language, material and graphic feasibility. The final result of the validator’s assessment of textbooks on subtheme I treat my body in grade I elementary school based on picture of the surrounding environment is 84,14 and included in the category very feasible for use in the learning process of grade I students of elementary school.